Design and Validation of Augmented Reality–Based Assessment to Measure Students’ Multiple Representation Ability - Astuti, Resti Tri; Ravensky Yurianty Pratiwi; Ferlin Vionita (Orbital: Jurnal Pendidikan Kimia, 2025)
This study aims to develop and validate a test assessment design assisted by Augmented Reality to measure students’ multiple representation abilities. The development model used in this research is the 4D Model (Define, Design, Develop, and Disseminate). The research subjects were students of the Chemistry Education Study Program in the 2024/2025 academic year. The trial subjects consisted of 18 students. Product validation was carried out by three chemistry education experts. The data collection technique used was a questionnaire. The research instruments consisted of an expert validation questionnaire and a student response questionnaire. The data analysis technique employed a quantitative approach with predetermined criteria. The results showed that Validator 1 provided a score of 87.96%, Validator 2 92.59%, and Validator 3 84.26%. The results of the study show that the validation of the developed product obtained an average percentage of 88.27%, categorized as very valid. The small-scale trial gained an average percentage of 94.99%, classified as very practical. The medium-scale trial obtained an average percentage of 91.71%, also categorized as very practical. These findings indicate that the AR-assisted MBKM assessment for measuring students’ multiple representation skills is highly practical to use.